Carbon Footprint: A Bibliometric Analysis - Marvin, William; Yvonne Augustine (Technium Social Sciences Journal, 2025)
Purpose – Recent years have seen a shift in concentration towards global warming and climate change. The global community aims to reduce carbon emissions to address the climate catastrophe. Carbon activities, including carbon footprint and carbon neutrality, have garnered significant attention as essential measures in combating climate change, with various governments establishing their carbon neutrality objectives. Design/methodology/approach – This work aims to employ bibliometric analysis to investigate research hotspots and trends in carbon-related activity. It employs VOSviewer to do a comprehensive study of 59 publications associated with carbon-related activities worldwide. All literature is retrieved via the Scopus database. Findings – The results indicate a significant increase in the volume of publications related to carbon in recent years. Research on carbon neutrality exhibits considerable variation among nations and regions. China and the United Kingdom are the principal catalysts and innovators in carbon neutrality research. Implication/Limitation - Researchers in developing nations can utilize the study’s findings as a starting point for their own research on carbon footprints and to highlight current issues in the field.While the amount of study on carbon neutrality in developing nations is rather low, such as in Indonesia, where the local journals do not range in Scopus, there are not so many, can there be future research for researchers in Indonesia. Originality/value – Research has focused on carbon-related activities, including carbon footprint and carbon neutrality, as well as technological, policy, and economic dimensions. Additionally, agricultural practices, low-carbon initiatives, green building, and supply chain management are prominent areas of investigation. Future research may be informed by the findings of this study, which elucidates the present state of carbon-related activity research.